2022
DOI: 10.1136/neurintsurg-2021-018628
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of A3.2 and A2 traumatic thoracolumbar spine compression fractures using vertebral body stenting: a 63-patient series

Abstract: BackgroundPercutaneous treatments for spinal injury are underused by neuroradiologists and spine surgeons, mainly owing to a lack of data on indications.ObjectiveTo assess the safety and efficacy of vertebral body stenting (VBS) for post-traumatic A3.2 and A2 fractures (Magerl classification) and determine the factors that influence the improvements.MethodsWe retrospectively reviewed patients who underwent VBS to treat a single traumatic thoracolumbar fracture from 2010 to 2019. Kyphosis, loss of vertebral bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…A study had retrospectively evaluated the safety and efficacy of the VBS in patients with post-Frontiers in Bioengineering and Biotechnology frontiersin.org traumatic A3.2 and A2 type fractures (single traumatic thoracolumbar fractures) who were treated between 2010 and 2019. The results confirmed an improvement in posterior convexity and restoration of vertebral height in all patients (Salle et al, 2022). In a prospective study on type A1.3 and A3.1 fractures, the VBS offered satisfactory improvements in pain, function, posterior convexity correction, and even endplate repositioning in osteoporotic and traumatic fractures (Klezl et al, 2011).…”
Section: Vertebral Implantssupporting
confidence: 57%
“…A study had retrospectively evaluated the safety and efficacy of the VBS in patients with post-Frontiers in Bioengineering and Biotechnology frontiersin.org traumatic A3.2 and A2 type fractures (single traumatic thoracolumbar fractures) who were treated between 2010 and 2019. The results confirmed an improvement in posterior convexity and restoration of vertebral height in all patients (Salle et al, 2022). In a prospective study on type A1.3 and A3.1 fractures, the VBS offered satisfactory improvements in pain, function, posterior convexity correction, and even endplate repositioning in osteoporotic and traumatic fractures (Klezl et al, 2011).…”
Section: Vertebral Implantssupporting
confidence: 57%
“…Salle et al (24) reported that the kyphosis treatment was more effective on Magerl A3 and B2 fractures than on those classified as A2.3, as well as for fractures with slight posterior wall protrusion on the spinal canal regarding the treatment of traumatic thoracolumbar fractures regarding minimally invasive percutaneous stabilization plus BKP. Salle et al (25) also recommend using vertebral body stenting (VBS) rather than open surgery for A3.2 and A2 fractures at the thoracolumbar junction and in young patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, good results of other implant techniques for OVF have been reported in recent years. introduced vertebral augmentation techniques using intravertebral distraction devices, such as VBS, armed kyphoplasty and Spine Jack, could be effective in fracture reduction (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of the SJ device causes a preferential direction of the flow of the PMMA reducing the risk of leakage. However, the current common belief is that VBS offers better containment of the cement than all other devices, since it remains within the stent; preventing this way any leak through its mesh (10).…”
Section: Cement Leaksmentioning
confidence: 99%
“…The only data regarding PWP greater than 50% is that of non-osteoporotic post-traumatic fractures (10,15). To our knowledge, some of these studies have even managed post-traumatic fractures with PWP greater than 75%, with good postoperative results and without neurological deterioration.…”
Section: Posterior Wall Protrusion (Pwp)mentioning
confidence: 99%